Affective states and performance outcomes - the findings of preliminary research involving pentathletes - Samelko, A.; Guszkowska, M. (Polish Journal of Sport and Tourism, 2016)
The aim of this article is to discuss the relationship between affective states experienced by athletes and the outcome of their performance. The article presents the findings of a pilot study which made it possible to determine the relationship between the emotional states, mood, and level of stress of a group of pentathletes and the outcomes they achieved in a sports competition. Material and methods. The study involved 12 senior modern pentathletes, including 7 male and 5 female athletes. The following standard psychology questionnaires were used in the study: the 10-item Perceived Stress Scale (PSS-10), the Positive and Negative Affect Schedule (PANAS), and the Profile of Mood State (POMS). Performance was assessed based on the number of points achieved by the pentathletes in particular events in the pentathlon, which are held according to the rules set by the International Modern Pentathlon Union (UIPM). Results. The findings of the study confirmed that there was a correlation between the athletes` mood and emotions and the outcome of their performance. The level of stress strongly negatively correlated with both the outcome they expected to achieve and the one they actually achieved for the combined event (running and shooting). For this event a relationship was also found between the athletes` affective states and their outcomes: in running and shooting there was a positive and statistically significant correlation between the level of positive emotions and anger and the results achieved. However, friendliness, one of the other affective state variables that were measured, correlated negatively with the outcomes of the athletes` performance. Conclusions. In the group of pentathletes who participated in the study, a high level of anger was associated with better outcomes, and a high level of friendliness had an adverse effect on the results achieved. The findings of the current study confirm that there is a relationship between affective states and performance outcomes, but the findings do not correspond with Morgan`s iceberg profile.